Śrītukārāmacaritāmrta : abhaṅgānta gailelẽ - Pāṅgārakara, Lakshmaṇa Rāmacandra (SAMP early 20th-century Indian books project, 1920)
Verse work on life of Tukārāma, ca. 1608-ca. 1649, Marathi saint poet.